Urban Forestry in Tiruppur - An Example of Successful Peoples' Participation - Sekar, T. (Indian Forester, 2006)
The ever increasing urban population coupled with growth of industries and the associated developments in the transport and service sectors are creating enormous stress on the natural resources by way of enhanced emission of air pollutants and discharge of effluents. Amelioration of urban environmental condition and buffering of climate in highly polluted atmosphere calls for systematic and sustained creation of green cover in form of green belts, avenues, tree islands etc in all vacant places of urban localities. Urban forestry differs from conventional plantation programmes in the forest areas in many ways, requiring application of multi managerial system and an altogether different management style. Public partnership is increasingly felt as the best option for ensuring greater success and lasting impact in the urban greening scenario across the country. As public finances from local bodies and government departments may not always match the total requirement for urban planting, the share of private contribution in this effort is expected to accelerate the pace of achieving the targets set for multi objective programme like urban forestry. This paper discusses issues connected with urban forestry in this light by analysing a case study from Tiruppur municipal town of Coimbatore District, Tamil Nadu.